Cover Image. (13th November 2019) - Kawajiri, Akihisa; Kitano, Shigehisa; Maeshima, Akiko Miyagi; Inamoto, Yoshihiro; Tajima, Kinuko; Takemura, Tomonari; Tanaka, Takashi; Ito, Ayumu; Okinaka, Keiji; Kurosawa, Saiko; Kim, Sung‐Won; Taniguchi, Hirokazu; et al.
Abstract : The cover image is based on the Original Article * Association of CD204 + macrophages with poor outcomes of malignant lymphomas not in remission treated by allogeneic HCT by Shigehisa Kitano** et al., https://doi.org/10.1111/ejh.13324 .***